The Role Of Strategic Communication In The Successful Implementation Of Public Policy: A Case Study In Makassar City Government - Asmansyah; Nurfadila (Jurnal Ilmu Sosial dan Humaniora, 2026)
Advances in digital technology have encouraged local governments in Indonesia to adopt the concept of smart cities to improve the quality of public services. In Makassar, implementation is carried out through e-government, digital service portals, and public applications. This implementation still faces obstacles in the form of low public participation, limited digital literacy, and less optimal policy socialization. This research aims to analyze the role of strategic communication in increasing public understanding and participation in digital services. The method used is descriptive qualitative with in-depth interview techniques, observation, and documentation studies of the government, service managers, and the community. The results of the study show that strategic communication through digital media, direct socialization, and community collaboration increase awareness and use of services. Participatory approaches have proven effective, although low digital literacy and information inconsistencies are still barriers. This study concludes that strategic communication plays an important role in the successful implementation of smart cities through inclusive and sustainable strategies.